Effect of a nutrition compound (honey and water) on blood glucose, body temperature and some physiological variables in wrestlers - Sabry Mohamed Yosef, E.; Nader Shalaby, M. (World Journal of Sport Sciences, 2010)
Many specialists advise athletes to have vitamins, minerals and nutrition compounds to enhance sports performance. Honey is one of the best sources of sugar that provides the body with energy quickly without side effects and for prolonged periods of time. Two thirds of the human body consists of water. So, it is considered as a nutrient. The human body loses 1.5 liters of water each day through the skin, lungs, intestines and kidneys (as urine). During training, a wrestler loses huge amounts of water through the skin, due to the high intensity training load. This affects the vital functions of internal body systems as the body loses water and body temperature increases accordingly. Also, heavy sweat lost during training and the increase of internal and external body temperature affects the ability of the wrestler to continue training and competition. The current study tries to decrease the skin temperature and maintaining blood glucose using a compound of honey and water. The researchers used the quasi-experimental approach (one experimental group and pre and post- measurements) on a sample of 7 wrestlers from Baladiat Al-Mahalla Sports Club. Results indicated that the recommended honey and water compound had a significant effect on blood glucose and decreasing skin temperature during training. The recommended compound did not affect internal body temperature.